SAT-014 Insulin Treatment in Human Pregnancy Mitigates an Increased Risk of Postpartum Psychological Distress with Maternal Obesity in the Absence of a Pre-Existing Mood and Anxiety Disorder - Jarmasz, Jessica S (J Endocr Soc, 2020)
BACKGROUND: Pregnant women with obesity are at increased risk for peripartum depression. Maternal obesity is also associated with reduced human placental lactogen (hPL) levels, and decreased hPL transcripts were reported in women with clinical depression. In addition, hPL production may be rescued in women with obesity that were subsequently diagnosed with gestational diabetes and treated with insulin (INS). Objective: Study the effect of INS treatment in pregnancy on the risk for postpartum psychological distress (PPD) in women with and without obesity. Study Design: Using data housed at the Manitoba Centre for Health Policy (2002–2017), cohorts of women (ages 15+) with a single live birth with and without obesity were developed using weight (≥85 and <65.6 kg, respectively) and an average (1.63 m) height. Pre-existing mood and anxiety disorders within 5 years preceding delivery as well as gestational hypertension were excluded. After randomly selecting 1 birth per mother, cohorts were stratified by INS treatment during the gestational period. The risk of PPD within 1 year of delivery was assessed by Poisson regression analysis. Models were adjusted for maternal age and area-level income at delivery. Results: The risk of PPD was 27% greater among women with obesity versus without (adjusted rate ratio (aRR)=1.27, 95% CI 1.16–1.4, p<0.0001). However, women with obesity treated with INS did not have a significantly different risk of PPD compared to women without obesity whether treated with INS (aRR=0.99, 95%CI 0.48–2.02, p=0.974) or not (aRR=1.16, 95%CI 0.86–1.56, p=0.328). This suggests that the risk of PPD among women with obesity may be reduced by INS treatment; however, our ability to detect a significant difference may be limited by small cohort numbers (46 women with obesity received INS in pregnancy) or confounders for receiving INS in pregnancy. Direct comparison of INS treatment within weight groups faced the same limitations but trended toward a reduction in women with obesity who received INS (aRR=0.91, 95%CI 0.68–1.22, p=0.531). The positive association between INS treatment in pregnancy and decreased risk of PPD in women with obesity was lost when pre-existing mood and anxiety disorder was not excluded. Inclusion of pre-existing diabetes in the adjusted models did not improve model fit or contribute significantly to the differences in PPD rates. Conclusions: Maternal obesity increases the risk for PPD but this risk may be reduced by gestational INS treatment in the absence of a pre-existing mood and anxiety disorders. This correlates with the decrease and increase in hPL levels reported previously with maternal obesity without and with INS treatment (for diabetes) in pregnancy, respectively. Thus, hPL levels may serve as a possible indicator of PPD risk and a potential target for gestational INS treatment.